Assessing the application of Optical-PhotoThermal Infrared spectroscopy for single-grain chemical palynology - Laura Scoble; Hao Meng; Simon J. Ussher; Mark F. Fitzsimons; Lauren Ansell; Mustafa Kansiz; Billy Simmonds; Nick Stone; Ralph M. Fyfe (Review of Palaeobotany and Palynology, 2026)

The occurrence and biogeochemical cycling of quaternary, ternary and volatile amines in marine systems - Mark F. Fitzsimons; Ruth Airs; Yin Chen (Frontiers in Marine Science, 2024)
This review provides a critical assessment of knowledge regarding the occurrence and behaviour of volatile, low molecular weight amines, particularly methylamines and quaternary amines, in marine aquatic systems. It provides an up-to-date evaluation of their presence within marine ecosystems, the processes likely to control their flux across the sea-air interface, and analytical techniques associated with their measurement. Interest in the occurrence and cycling of these groups of compounds in seawater has increased within the last 10–15 years, due to their potential role in climate regulation. As such, the need for wider measurements and mechanistic studies to elucidate their role within biological communities and, more widely, the nitrogen cycle and marine ecosystem models, is apparent. Finally, we make recommendations on what research questions are most suitable for future studies in this area.

Biochar improves fertility in waste derived manufactured soils, but not resilience to climate change - Jennifer M. Rhymes; Daniel Evans; Giuliano Laudone; H. Kate Schofield; Ellen Fry; Mark F. Fitzsimons (Science of The Total Environment, 2024)

Optimisation of classification methods to differentiate morphologically-similar pollen grains from FT-IR spectra - Laura Scoble; Simon J. Ussher; Mark F. Fitzsimons; Lauren Ansell; Matthew Craven; Ralph M. Fyfe (Review of Palaeobotany and Palynology, 2024)

The determination of volatile amines in aquatic marine systems: A review - Mark F. Fitzsimons; Mia Tilley; Charlotte H.L. Cree (Analytica Chimica Acta, 2023)

Processes of distribution of pharmaceuticals in surface freshwaters: implications for risk assessment - Simone Bagnis; Mark F. Fitzsimons; Jason Snape; Alan Tappin; Sean Comber (Environmental Chemistry Letters, 2018)

Does carbon limitation reduce nitrogen retention in soil? - H. Kate Schofield; Tim R. Pettitt; Alan D. Tappin; Gavyn K. Rollinson; Mark F. Fitzsimons (Environmental Chemistry Letters, 2018)

Unexpected removal of the most neutral cationic pharmaceutical in river waters - Alan D. Tappin; J. Paul Loughnane; Alan J. McCarthy; Mark F. Fitzsimons (Environmental Chemistry Letters, 2016)

Removal of atrazine from river waters by indigenous microorganisms - Alan D. Tappin; J. Paul Loughnane; Alan J. McCarthy; Mark F. Fitzsimons (Environmental Chemistry Letters, 2012)

Observed dissolved and particulate nitrogen concentrations in a mini flume - Simon J. Ussher; Andrew J. Manning; Alan D. Tappin; Mark F. Fitzsimons (Hydrobiologia, 2011)

A comparison of SEM-EDS with ICP-AES for the quantitative elemental determination of estuarine particles - Stephen M. Haley; Alan D. Tappin; Peter R. Bond; Mark F. Fitzsimons (Environmental Chemistry Letters, 2006)